MODEL DIRECT INSTRUCTION UNTUK MENGEMBANGKAN KEMAMPUAN PENETAPAN ANGKA KREDIT GURU SEBAGAI UPAYA PENINGKATAN KOMPETENSI CALON GURU SEJARAH PROFESIONAL - Ipong Jazimah; Arifin Suryo Nugroho (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2020)
ABSTRACTThe problems in this study are 1) How to apply the direct instruction model to developthe ability to determine teacher credit points as an effort to increase the competence ofprospective professional history teachers 2) What are the results of improving studentabilities that have been achieved by applying the direct instruction model 3) What arethe obstacles faced and how to attempt to solve it. This research uses a qualitativeapproach. Data sources consist of documents and informants. Documents in the form ofbooks, magazines, journals, pretest and posttest results. Data were collected byrecording documents, observations, and interviews. The data validity was done by meansof data triangulation. Data analysis used interactive analysis with three stages ofanalysis, namely data reduction, data presentation, and drawing conclusions. Thisresearch results in the conclusion that 1) The direct instruction learning model canimprove understanding of the material, 2) Studying the material for teacher credit scoresmakes education study program students more creative and innovative in creating newideas, 3) The need for educational study program students to be equipped with the abilitymaterial for teacher credit scores so that later when they become teachers they becomeprofessional teachers with teacher professional rank lines.Keywords: Direct instruction learning model, teacher credit score